Experimental study on laminar flame speeds and Markstein length of propane air mixtures at atmospheric conditions - Yousif, A.A. (Universiti Malaysia Pahang, 2015)
An experimental study is performed in this work to determine stretched and unstretched laminar flame propagation velocities, Lewis number, flame thickness and the Markstein length of propane-air mixtures. The spherical flame propagation method was used to achieve this experimental work. Non-premixed propane-air mixtures at ambient temperature 303Â±1 K, pressure of 0.1 MPa and equivalence ratios ranging from Î¦ = 0.6 to 1.4 were ignited in a cylindrical combustion chamber. The stretched laminar burning speed was found to increase with the flame radius and time from ignition, which was attributed to flame propagation development. This is achieved by high-speed schlieren cine photography for observation of the flames in the vessel. The results obtained show that the unstretched laminar flame velocity increased as the equivalence ratio increased, and the recorded value reached a maximum at equivalence ratio Î¦ = 1.0 and decreased at the rich region. It was found that, with increase of the equivalence ratio, the Markstein length is increased and decreased in lean mixtures. The present data were in good agreement with those previously published using different techniques. However, the difference between the peak value of laminar flame velocity in the present work and those in the literature is between 4-5.5. Â© Universiti Malaysia Pahang.